Motherhood and HIV: reproductive desire, ambivalent feelings and a/an (not) offered care - Clarissa Bohrer da Silva; Maria da Graça Corso da Motta; Renata Bellenzani (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To identify in the scientific literature the feelings of women living with HIV in relation to reproduction and motherhood, as well as the care provided by health professionals regarding reproductive health as a right. Method: Integrative review carried out in 2017, in the databases LILACS, PUBMED, BDENF and SciELO Virtual Library. We analyzed 30 articles. Results: As feelings, the motivation for reproduction and self-care, fears, uncertainties and hopes were evidenced. As care, services that support reproductive decisions were evidenced, but, predominantly, the disregard for the desire and care incipience for reproductive planning. Conclusion: There is no comprehensive and humanized work on the reproductive issues of these women, either through the neglect of the desire and viability of gestation or by the incipient care to the ambivalent emotional experiences. There is a need to qualify the care model in order to configure it, in fact, as care, aiming at guaranteeing reproductive rights.